Peningkatan laju multiplikasi tunas dan keragaan planlet Stevia rebaudiana pada kultur in vitro Increasing shoot multiplication rate and plantlet vigor of Stevia rebaudiana in vitro culture - . SUMARYONO; Masna Maya SINTA (E-Journal Menara Perkebunan, 2011)
AbstractStevia (Stevia rebaudiana Bertoni) is a natural zero-calorie sweetener plant grown in a high population density.Tissue culture technique is useful for rapid mass propagationof plants to provide superior planting materials. Experimentswere conducted to increase growth and multiplication ofshoots and vigor of plantlets of stevia. Explants used wereapical and axillary buds from plantlets grown on MS mediumwithout plant growth regulators. Combinations of BA andIAA at different concentrations were used for shoot growthand multiplication, whereas plant growth retardants(ancymidol and paclobutrazol) and light intensity were usedfor plantlet vigor. The results showed that stevia explantscultured on MS medium without plant growth regulatorsproduced the highest shoots (4.5 cm) with two shoots perexplant. The best multiplication rate of shoots were found onMS medium added with 1.13 mg/L BA combined with0.35 mg/L IAA which produced on average 4.5 shoots and11.9 nodes per initial explant. Ancymidol and paclobutrazolconcentrations affected significantly growth and vigor ofstevia plantlets. Increasing the concentration of ancymidoland paclobutrazol decreased plantlet height and biomassfresh weight, but increased stem diameter. Paclobutrazol at0.1 mg/L was the best treatment to increase the vigor ofstevia plantlets. Light intensity at 20 µmol/m 2 /s gave betterplantlet vigor than other light intensities. It can be concludedthat multiplication of stevia shoots should be grown on MSmedium supplemented with 1.13 mg/L BA + 0.35 mg/L IAAand the vigor of the shoots can be increased by culturing onMS medium containing 0.1 mg/L paclobutrazol underfluorescence lamps with 20 µmol/m 2 /s light intensity.AbstrakStevia (Stevia rebaudiana Bertoni) adalah tanamanpemanis alami nir-kalori yang ditanam dengan kerapatanpopulasi yang sangat tinggi. Teknik kultur jaringan dapatdigunakan untuk perbanyakan tanaman secara massal dancepat untuk menyediakan bahan tanam unggul. Penelitiantelah dilakukan untuk meningkatkan pertumbuhan danmultiplikasi tunas dan keragaan planlet stevia. Eksplan yangdigunakan adalah tunas pucuk dan tunas samping dari planletyang ditumbuhkan pada medium MS tanpa zat pengaturtumbuh. Kombinasi BA dan IAA dengan konsentrasi yangberbeda digunakan untuk pertumbuhan dan multiplikasitunas, sedangkan zat penghambat tumbuh (ansimidol danpaklobutrazol) serta intensitas cahaya digunakan untukkeragaan planlet. Hasil penelitian menunjukkan bahwaeksplan stevia yang ditumbuhkan pada medium MS tanpa zatpengatur tumbuh menghasilkan tunas paling tinggi (4,5 cm)dengan dua tunas per eksplan. Multiplikasi tunas terbaikdiperoleh pada medium dengan BA 1,13 mg/L yangdikombinasikan dengan IAA 0,35 mg/L yang menghasilkan4,5 tunas dan 11,9 ruas per eksplan awal. Konsentrasiansimidol dan paklobutrazol berpengaruh nyata terhadappertumbuhan dan keragaan planlet stevia. Meningkatnyakonsentrasi ansimidol dan paklobutrazol menurunkan tinggiplanlet dan bobot basah biomassa, tetapi meningkatkandiameter batang. Paklobutrazol pada konsentrasi 0,1 mg/Lmerupakan perlakuan terbaik untuk meningkatkan keragaanplanlet stevia. Intensitas cahaya pada 20 µmol/m 2 /detikmemberikan keragaan planlet yang lebih baik dibandingkanintensitas cahaya yang lain. Dapat disimpulkan bahwamultiplikasi tunas stevia sebaiknya dilakukan pada mediumMS ditambah BA 1,13 mg/L + IAA 0,35 mg/L dan keragaanplanlet dapat ditingkatkan dengan menanam planlet padamedium MS ditambah paklobutrazol 0,1 mg/L di bawahlampu fluoresen dengan intensitas cahaya 20 µmol/m 2 /detik.